Renewable energy sources - present realities and future options - عزت ثائر محي الدين (Journal of Economics and Administrative Sciences, 2011)
Renewable energy sources - realities of the present and future options Many of the directories indicate that the global energy system begin with a period of transition from total dependence on fossil energy sources, particularly oil, Into a new era in which renewable energy sources play an important role in meeting the growing needs of energy demand. There are many factors that will contribute to the strengthening of this trend towards transformation, which also will decide how quickly this transformation of renewable energy systems effectively in the global system of energy demand. These factors, In brief: the size of environmental pollution and climatic changes resulting from the excessive use of fossil fuels, the size of reserves of fossil fuels and the amount of new additions to her and to oil in particular, Amount of support and funding for renewable energy sources and, finally, other political factors linked to the concept of energy security, especially for the major industrialized importing oil countries. The disposition of any country requires to keep pace with these changes and seek to support efforts to introduce renewable energies within the system of energy production gradually so as not to lag behind in global development.